1985
DOI: 10.1128/jcm.22.6.1035-1039.1985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Yersinia enterocolitica antigen common to enterocolitis-associated serotypes

Abstract: Yersinia enterocolitica synthesized an exocellular antigen common to the serotypes associated with enterocolitis but absent from other serotypes or from other Yersinia species. Both virulent Ca2+-dependent and avirulent Ca2+-independent isogenic pairs derived from the enterocolitis-associated serotypes synthesized the common antigen. Requirements for the synthesis of this common antigen were (i) the presence of metabolizable sugars and (ii) growth on a solid medium at 37°C. The antigen was identified as a 24,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Recently, we have shown that representative strains of the pathogenic serogroups of Yersinia enterocolitica but not of the avirulent serogroups or other species of Yersinia synthesize a 24,000-dalton (Da) plasmid-independent protein when grown on a solid medium at 37°C with a metabolizable carbohydrate (2). This protein behaves as a surface antigen, but it is not a membrane protein and remains only loosely attached to the cell (2). In the present study, we have extended those findings by examining whether the 24,000-Da protein is synthesized only by strains associated with enterocolitis.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Recently, we have shown that representative strains of the pathogenic serogroups of Yersinia enterocolitica but not of the avirulent serogroups or other species of Yersinia synthesize a 24,000-dalton (Da) plasmid-independent protein when grown on a solid medium at 37°C with a metabolizable carbohydrate (2). This protein behaves as a surface antigen, but it is not a membrane protein and remains only loosely attached to the cell (2). In the present study, we have extended those findings by examining whether the 24,000-Da protein is synthesized only by strains associated with enterocolitis.…”
supporting
confidence: 54%
“…The staphylococci were prepared and sensitized with the 24,000-Da antiserum as described by Kronvall (4). The preparation of the antiserum has been described previously (2); as tested by Western blot and immunoelectrophoresis, it contained antibodies to the 24,000-Da protein but not to other surface or cytoplasmic antigens. For coagglutination, duplicates of each isolate were inoculated either in Trypticase soy agar (BBL Microbiology Systems) or in the same medium supplemented with 0.25% glucose and 0.25% sucrose and grown for 24 h at 37°C.…”
mentioning
confidence: 99%
“…Some time ago, Diaz and co-workers described another temperature-induced surface antigen common to the pathogenic serotypes of V. enterocotitica. This antigen, called C-Ag is a 24 kDa protein synthesized when the bacteria are grown on a solid medium supplemented with a metabolizable sugar (Diaz et al. 1985;Toyos etal., 1986).…”
Section: Introductionmentioning
confidence: 99%